2003
DOI: 10.1016/s1044-0305(02)00904-2
|View full text |Cite
|
Sign up to set email alerts
|

Ketalization of phosphonium ions by 1,4-dioxane: Selective detection of the chemical warfare agent simulant DMMP in mixtures using ion/molecule reactions

Abstract: Phosphonium ions CH(3)P(O)OCH(3)(+) (93 Th) and CH(3)OP(O)OCH(3)(+) (109 Th) react with 1,4-dioxane to form unique cyclic ketalization products, 1,3,2-dioxaphospholanium ions. By contrast, a variety of other types of ions having multiple bonds, including the acylium ions CH(3)CO(+) (43 Th), CH(3)OCO(+) (59 Th), (CH(3))(2)NCO(+) (72 Th), and PhCO(+) (105 Th), the iminium ion H(2)C[double bond]NHC(2)H(5)(+) (58 Th) and the carbosulfonium ion H(2)C[double bond]SC(2)H(5)(+) (75 Th) do not react with 1,4-dioxane un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…The selective ion/molecule reactions of the oxygen-bonded Meisenheimer complexes are reminiscent of the selective phosphorus ester chemistry used to recognize chemical warfare agents [20]. In both this and in the earlier experiments, constant neutral loss/gain scans proved useful in examining complex mixtures for compounds containing the specific functional group of interest.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The selective ion/molecule reactions of the oxygen-bonded Meisenheimer complexes are reminiscent of the selective phosphorus ester chemistry used to recognize chemical warfare agents [20]. In both this and in the earlier experiments, constant neutral loss/gain scans proved useful in examining complex mixtures for compounds containing the specific functional group of interest.…”
Section: Discussionmentioning
confidence: 95%
“…Like Table 1. [19,20] can be adopted to detect these two unique transitions for TNT. As a demonstration, a mixture of ethyl isovalerate, 2,4-dimethyl-3-hexanone and TNT was ionized using the hemiacetal CH 3 OCH 2 OH as the reagent gas.…”
Section: Carbon-bonded Meisenheimer Complexesmentioning
confidence: 99%
“…Benzomorpholine, 3,4-dihydro-2H-1,4-benzoxazine, is a constituent of many naturally occurring substances [46]. An earlier study [51] from this laboratory reported that arenesulfenylium cation PhS ϩ can undergo the Eberlin reaction with 2,2-dimethyl-1,3-dioxolane, a cyclic ketal and form a characteristic four-membered cyclic product, 2-aryl-1,2-oxathietan-2-ium ion (the prototype Eberlin reaction [52][53][54][55] is the gas-phase transacetalization of acylium ions RCO ϩ by cyclic acetals or ketals, as shown in Scheme 7). It is therefore important to seek new simple routes for the synthesis of benzomorpholine.…”
Section: Synthesis Of N-heterocycles Using Arylnitrenium Ionsmentioning
confidence: 99%
“…This results in three-to-fivemembered ring expansion to yield cyclic 1,3-dioxolanylium ions [21][22][23]. This structure-selective reaction, which displays many features common to those of transacetalization reactions of acylium ions with acetals and analogs [1], has been demonstrated to be very useful for both characterization and selective screening of specific compounds such as warfare agents [24].…”
mentioning
confidence: 99%